Dose findings of antofloxacin hydrochloride for treating bacterial infections in an early clinical trial using PK-PD parameters in healthy volunteers - Li Yun-fei; Wang Kun; Yin Fang; He Ying-chun; Huang Ji-han; Zheng Qing-shan (Acta Pharmacologica Sinica, 2016)
Aim: To find an appropriate dose regimen of the novel antibacterial agent antofloxacin for a phase II clinical trial using a population pharmacokinetic (PPK) study in healthy volunteers and the minimum inhibitory concentration (MIC) as pharmacodynamic (PD) parameters. Methods: Twenty-four healthy volunteers were enrolled in a double-blind crossover study and received antofloxacin (200 or 400 mg/d, po) for consecutive 5 d with 10 d washout between two separate periods. Blood concentrations were analyzed using HPLC with a UV-Vis detector. The values of area under the curve (AUC) with covariates were obtained from a PPK model, and the MICs came from the previous in vitro studies. The dose regimen was determined for the phase II clinical trial according to the ratio (>20) of AUC/MIC, and the efficacy of the dose was evaluated by the trial. Results: A two-compartment model best described the time-concentration data with first-order absorption. The PPK parameter estimates for CL, Vc, Q, Vp and KA are 8.34 L/h, 142 L, 15.9 L/h, 52.2 L and 4.64 1/h, respectively. The covariates sex for KA, weight for CL, weight for Vc and interoccasion variability were included in the final model. The AUC/MIC was calculated based on the PPK model and the MIC of antofloxacin for Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus and Staphylococcus epidermidis were determined in previous researches. The 400 mg loading dose with 200 mg/d maintenance dose was recommended and confirmed by the phase II trial. Conclusion: The ratio of AUC from the PPK model vs MIC as the PD parameter can be applied in a dose-finding trial of antofloxacin in treatment of bacterial infections. The PPK model suggests that sex and body weight may be considerations in regards to individual therapy, which should be investigated in larger clinical trials and serve as a potential reference for clinical therapies.